Biological treatment with fungi of olive mill wastewater pre-treated by photocatalytic oxidation with nanomaterials - Nogueira, V.
Olive mill wastewater (OMW) still is a major environmental problem due to its high chemical oxygen demand (COD) and total phenolic content (TPC), contributing for the high toxicity and recalcitrant nature. Several attempts have been made for developing more efficient treatment processes, but no chemical or biological approaches were found to be totally effective, especially in terms of toxicity reduction. In this context, the main purpose of this study was to investigate the treatability of OMW by the combination of photocatalytic oxidation, using two nanomaterials as catalysts (TiO2 and Fe2O3), with biological degradation by fungi (Pleurotus sajor caju and Phanerochaete chrysosporium). Photocatalytic oxidation was carried out using different systems, nano-TiO2/UV, nano-Fe2O3/UV, nano-TiO2/H2O2/UV and nano-Fe2O3/H2O2/UV. The effectiveness of the treatment was assessed through color (465 nm), aromatics (270 nm), COD and TPC reductions, as well as by the decrease in toxicity using the bacterium Vibrio fischeri. The chemical treatment with the system nano-TiO2/H2O2/UV promoted 43%, 14%, 38% and 31% reductions in color, aromatics content, COD and TPC, respectively. However no toxicity reduction was observed. The combination with a biological treatment increased the reduction of COD and TPC as well as a reduction in toxicity. The treatment with P. chrysosporium promoted the highest reduction in toxicity, but P. sajor caju was responsible for the best reduction in COD and TPC. However, the biological treatment was more effective when no hydrogen peroxide was used in the pre-treatment.